R-T-B magnet powder and its manufacturing method
A novel method for producing Nd-Fe-B magnet powder with small particle size and narrow distribution addresses the issue of coarse particles and high-temperature coercivity loss, enhancing magnetic properties while reducing costs by omitting heavy rare earths.
Patent Information
- Application Number
- JP2021048896
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-23
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-03-23
AI Technical Summary
Existing methods for producing Nd-Fe-B magnet powder result in wide particle size distributions, leading to coarse particles due to abnormal grain growth during sintering, which affects the coercive force, especially at high temperatures, and rely on expensive and supply-unstable heavy rare earth elements.
A method involving the use of rare earth metal, transition metal, and boron halides, followed by a heat treatment process to produce an R-T-B alloy powder, which is then cleaned and optionally dehydrogenated, resulting in a magnet powder with a small average particle diameter and narrow particle size distribution, without relying on heavy rare earth elements.
The method produces magnet powder with an average particle diameter of 0.1 to 1.0 μm and a narrow particle size distribution, improving magnetic properties and reducing production costs by avoiding heavy rare earth elements.
Smart Images

Figure 0007609669000001 
Figure 0007609669000002 
Figure 0007609669000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to R-T-B based magnet powder and a method for producing the same. [Background technology]
[0002] Among R-T-B permanent magnets, Nd-Fe-B sintered magnets have excellent magnetic properties and are therefore mounted, for example, in motors, generators and actuators. Nd-Fe-B sintered magnets used in motors and other applications are required to have high coercivity even in high-temperature environments. However, the coercivity of Nd-Fe-B sintered magnets decreases as the temperature rises. The coercivity of Nd-Fe-B permanent magnets at high temperatures is determined by the main phase, Nd2Fe 14 The magnetic properties of Nd-Fe-B permanent magnets can be increased by replacing a part of the Nd element constituting the B phase with a heavy rare earth element (Dy, Tb, etc.). However, heavy rare earth elements are expensive, and the price and supply of heavy rare earth elements are unstable. Therefore, in order to reduce manufacturing costs and management risks, it is desirable to improve the magnetic properties of Nd-Fe-B permanent magnets without using heavy rare earth elements.
[0003] It is generally known that the smaller the particle size of the main phase particles in a sintered magnet, the easier it is to improve its magnetic properties, especially its coercive force. In order to reduce the particle size of the main phase particles, it is necessary to reduce the average particle size of the magnet powder, which is the raw material for the sintered magnet. Conventionally, Nd-Fe-B alloy powder is produced by pulverizing alloys produced by the strip casting method in a jet mill using argon gas or nitrogen gas. However, due to the pulverization limit, it is usually not possible to obtain magnet powder with an average particle size of 1 μm or less.
[0004] Patent Documents 1 and 2 disclose a method for producing magnet powder having an average particle size of 1.0 μm or less by a jet mill pulverization method using helium gas. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2017 / 022684 [Patent Document 2] International Publication No. 2014 / 142137 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the magnet powders produced by the methods disclosed in Patent Documents 1 and 2 have a wide particle size distribution, and therefore the particle size of the main phase particles in the resulting sintered magnet becomes coarse due to abnormal grain growth after sintering caused by the variation in particle size of the magnet powder.
[0007] One aspect of the present invention has been made in consideration of the above circumstances, and has an object to provide a method for producing magnetic powder having a small average particle size and a narrow particle size distribution, and a novel magnetic powder. [Means for solving the problem]
[0008] One aspect of the present invention includes a heat treatment step of obtaining an R-T-B system alloy powder by heating a composition containing a rare earth metal element R, a transition metal element T, boron B, and at least one metal halide selected from the group consisting of halides of alkali metal elements, halides of alkaline earth metal elements, and halides of rare earth metals, at a temperature equal to or higher than the melting point of the metal halide, The rare earth metal element R is at least one selected from the group consisting of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; The method for producing R-T-B system magnet powder is characterized in that the transition metal element T is at least one selected from the group consisting of Fe, Ni, Co, Cr, and Mn.
[0009] In one embodiment, the above-mentioned production method may further include a washing step of washing the R-T-B system alloy powder with a washing liquid in which the metal halide is dissolved.
[0010] In one embodiment, the cleaning solution may include a solvent that does not have a hydroxy group.
[0011] In one embodiment, the cleaning solution may include at least one selected from the group consisting of formamide and dimethylformamide.
[0012] Another aspect of the present invention is a method for producing a semiconductor device comprising: The average particle size is 0.1 to 1.0 μm, Particle size distribution width (D 90 -D 10 ) / D 50 is less than or equal to 0.85, The rare earth metal element R is at least one selected from the group consisting of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; The R-T-B magnet powder is one in which the transition metal element T is at least one selected from the group consisting of Fe, Ni, Co, Cr and Mn. (However, D 10 , D 50 and D. 90 are respectively the particle sizes at which the cumulative frequency is 10%, the particle sizes at which the cumulative frequency is 50%, and the particle sizes at which the cumulative frequency is 90% in the area-based cumulative particle size distribution curve based on image analysis of scanning electron microscope (SEM) images of R-T-B magnet powder.)
[0013] In one embodiment, the magnet powder is 14 It may contain single crystal particles of B.
[0014] In one embodiment, the magnetic powder may have a circularity of more than 70%.
[0015] In one embodiment, the magnet powder may have a Ca content of 100 ppm by mass or less.
[0016] In one embodiment, the magnet powder may have a Cl content of 1 ppm by mass or more and 50,000 ppm by mass or less. Effect of the Invention
[0017] According to one aspect of the present invention, there is provided a method for producing a magnet powder having a small average particle size and a narrow particle size distribution, and a novel magnet powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.
[0019] [Manufacturing method of R-T-B magnet powder] The method for producing the RTB based magnet powder according to this embodiment (hereinafter simply referred to as the "production method according to this embodiment") will be described below.
[0020] In this specification, powder refers to an aggregate of particles.
[0021] (Heat treatment process) The manufacturing method according to this embodiment includes a heat treatment step of obtaining an R-T-B type alloy powder by heating a composition containing a rare earth metal element R, a transition metal element T, boron B, and at least one metal halide (hereinafter simply referred to as a "metal halide") selected from the group consisting of halides of alkali metal elements, halides of alkaline earth metal elements, and halides of rare earth metals, at a temperature equal to or higher than the melting point of the metal halide.
[0022] R is at least one selected from the group consisting of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu.
[0023] R may be a metal or an alloy. Examples of the form of R include powder, granules, and blocks (ingots).
[0024] T is at least one selected from the group consisting of Fe, Ni, Co, Cr and Mn.
[0025] T may be a simple metal, an alloy, or a compound. Examples of the form of T include powder, granules, and chunks (ingots). Since the average particle size of the resulting magnet powder tends to be small, powder is preferred, and fine powder with an average particle size of 1 μm or less is particularly preferred.
[0026] B may be a metal element, an alloy, or a compound. Examples of the form of B include powder, granules, and blocks (ingots).
[0027] Examples of metal halides include fluorides, chlorides, bromides, and iodides. Examples of alkali metal halides include LiCl, KCl, NaCl, and LiF. Examples of alkaline earth metal halides include CaCl2, MgCl2, BaCl2, and SrCl2. Examples of rare earth metal halides include NdCl3, SmCl3, and CeCl3. Examples of the form of metal halides include powder.
[0028] In the production method according to this embodiment, when R and T are Nd and Fe, respectively, it is possible to produce an Nd-Fe-B based alloy powder.
[0029] In the present specification, when the metal halide is a mixture, a temperature equal to or higher than the melting point of the metal halide means a temperature equal to or higher than the eutectic point of the mixture as shown in a phase diagram.
[0030] The temperature for the heat treatment is not particularly limited as long as it is equal to or higher than the melting point of the metal halide, and may be, for example, 300° C. or higher and 1200° C. or lower.
[0031] The heat treatment time may be from 0.5 hours to 6 hours.
[0032] The concentration of R based on the total amount of metal halides at the heat treatment temperature may be, for example, 3.2 mol / L or more and 8.2 mol / L or less.
[0033] The manufacturing method according to the present embodiment may or may not include a step other than the heat treatment step described above. When the manufacturing method according to the present embodiment does not include a step other than the heat treatment step described above, the alloy powder obtained in the heat treatment step can be used as magnet powder.
[0034] (Cleaning process) The manufacturing method according to this embodiment may further include a cleaning step of cleaning the R-T-B system alloy powder with a cleaning liquid in which a metal halide is dissolved.
[0035] The washing method in the washing step is not particularly limited as long as it is a method that can remove metal halides. For example, a method in which a washing liquid is added to the R-T-B alloy powder, the mixture is stirred, and then decanted can be repeatedly used.
[0036] The cleaning liquid is not particularly limited as long as it is a solvent in which the metal halide dissolves, and may be a solvent having a hydroxyl group or a solvent having no hydroxyl group. The cleaning liquid is preferably a solvent having no hydroxyl group, since it can suppress oxidation of the obtained R-T-B alloy powder. Examples of the solvent having a hydroxyl group include water, methanol, ethanol, and glycol-based solvents such as ethylene glycol. Examples of the solvent having no hydroxyl group include formamide, dimethylformamide, dimethylacetamide, acetonitrile, dimethylsulfoxide, acetone, acetylacetone, and ethylene carbonate. Formamide and dimethylformamide are preferable because they have high solubility of metal halides and can efficiently remove metal halides. The cleaning liquid may use one type of solvent alone or two or more types of solvents in combination. The content of the solvent having no hydroxyl group in the cleaning liquid may be 60 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, 95 mass% or more, or 100 mass%.
[0037] (Dehydrogenation process) When a solvent having a hydroxyl group is used as the cleaning liquid, hydrogen may enter between the crystal lattices of the RTB alloy powder. In this case, the manufacturing method according to the present embodiment may further include a dehydrogenation step of dehydrogenating the RTB alloy powder.
[0038] The method for dehydrogenating the RTB alloy powder is not particularly limited, but examples thereof include a method in which the RTB alloy powder is heat-treated in a vacuum or in an inert gas atmosphere.
[0039] The temperature of the heat treatment in the dehydrogenation step may be 150 to 250° C. The time of the heat treatment may be 1 to 3 hours.
[0040] (drying process) When the manufacturing method according to this embodiment includes a cleaning step, it may further include a drying step of removing the cleaning liquid from the R-T-B system alloy powder by drying the R-T-B system alloy powder.
[0041] The temperature at which the R-T-B alloy powder is dried is preferably from room temperature (20° C.) to 200° C., since this can suppress oxidation of the R-T-B alloy powder. The atmosphere during drying may be, for example, an inert gas such as argon or nitrogen, or a vacuum.
[0042] (Crushing process) The manufacturing method according to this embodiment may further include a pulverization step of pulverizing the R-T-B alloy powder. The pulverization method is not particularly limited, but examples thereof include pulverization using a jet mill, a dry or wet ball mill, a vibration mill, and a media stirring mill.
[0043] [Effects] The manufacturing method according to the above embodiment includes a heat treatment step of heating the composition at a temperature equal to or higher than the melting point of the metal halide. Unlike R contained in the composition, B is generally considered to be difficult to dissolve in a metal halide melt due to its high electronegativity. However, the inventors have found through their research that the composition dissolves in a metal halide melt even when it contains B by combining R and a metal halide with B. Then, the composition is heated at a temperature equal to or higher than the melting point of the metal halide, and R and B dissolved in the metal halide melt diffuse into T, thereby obtaining an RTB-based alloy at a lower temperature than before, and producing a magnet powder with a small average particle size and a narrow particle size distribution.
[0044] [R-T-B magnet powder] The RTB based magnet powder according to this embodiment (hereinafter simply referred to as "the magnet powder according to this embodiment") will be described below.
[0045] The magnet powder according to the present embodiment contains a rare earth metal element R, a transition metal element T, and boron B, has an average particle size of 0.1 to 1.0 μm, and has a particle size distribution width (D 90 -D 10 ) / D 50 is 0.85 or less, R is at least one selected from the group consisting of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu, and T is at least one selected from the group consisting of Fe, Ni, Co, Cr, and Mn.
[0046] The average particle size of the magnet powder according to this embodiment is 1.0 μm or less, and from the viewpoint of improving the magnetic properties, it is preferably 0.8 μm or less, and more preferably 0.6 μm or less. The method for measuring the average particle size will be described later.
[0047] The particle size distribution width (D 90 -D 10 ) / D 50is not more than 0.85, and from the viewpoint of improving the magnetic properties, is preferably not more than 0.80, and more preferably not more than 0.75. The method for measuring the particle size distribution width will be described later.
[0048] The circularity of the magnetic powder according to this embodiment is preferably more than 70%, and more preferably more than 72%, because this improves the fluidity when molding the magnetic powder. The method for measuring the circularity will be described later.
[0049] The average particle size, particle size distribution width, and circularity of the magnet powder according to this embodiment are measured as follows. That is, an R-T-B magnet powder and a thermosetting resin are mixed in approximately equal amounts by volume to obtain a mixture. The obtained mixture is applied onto a sample stage (pin stub) for FIB (Focused Ion Beam), vacuum degassed, and then heated at 120°C for 1 hour using a hot plate to harden the mixture, thereby obtaining a hardened product. The surface of the hardened product is then dry-polished with abrasive paper. The hardened product is first roughly polished with coarse abrasive paper (#600), then further polished with medium-roughness abrasive paper (#1200), and finally finish-polished with fine abrasive paper (#3000), thereby obtaining a measurement sample with a mirror-finished polished surface. The obtained measurement sample is observed with a SEM (Scanning Electron Microscope) to obtain an SEM image. The observation magnification is 10,000 times. Randomly select 300 particles from the magnetic powders that can be confirmed in the SEM image. For the selected magnetic powders, the area S and perimeter L of the magnetic powders are measured using image analysis and image measurement software. Then, the particle diameter D, particle size distribution width, and circularity coefficient, which are respectively defined by the following formulas (1) to (3), are calculated. Here, D 10 , D 50 and D. 90 are the particle diameters at which the cumulative frequency is 10%, 50%, and 90%, respectively, in the area-based cumulative particle diameter distribution curve of 300 magnet powder particles. The area-based average value of the particle diameters D of the 300 magnet powder particles is defined as the average particle diameter of the magnet powder, and the number-based average value of the circularity coefficients of the 300 magnet powder particles is defined as the circularity of the magnet powder.
[0050]
number
[0051] The magnet powder according to this embodiment has improved remanent magnetization, so R2T 14 It is preferable that the magnet powder according to the present embodiment contains single crystal particles of R2T 14 The presence of single crystal particles of B can be confirmed as follows. That is, a measurement sample with a mirror-polished surface is obtained in the same manner as in the measurement of the average particle size of the magnet powder described above. The measurement sample is sliced by focused ion beam processing. The obtained slice is observed with a TEM (Transmission Electron Microscope). The observation magnification is 50,000 times. The selected area diffraction image observed by TEM is spot-shaped, and R2T 14 If the crystal structure of B matches P42 / mmm, the magnet powder is R2T 14 It is determined that the sample has single crystal particles of B.
[0052] In the present specification, a single crystal particle refers to an isolated particle that does not contain crystal grain boundaries therein, has a uniform crystal orientation, and is not aggregated with other particles.
[0053] In the magnet powder according to this embodiment, the Ca content is preferably 100 mass ppm or less, 10 mass ppm or less, 1 mass ppm or less, or 0.1 mass ppm or less, because the Ca content improves remanence. The Ca content can be measured using ICP-AES (Inductively Coupled Plasma Atomic Emission Spectroscopy).
[0054] In the magnet powder according to this embodiment, the Cl content is preferably 1 ppm by mass or more and 50000 ppm by mass or less, since this can suppress oxidation of the powder. The Cl content can be measured using ICP-AES.
[0055] In the magnet powder according to this embodiment, the C content is preferably 1000 mass ppm or less, since this further improves the magnetic properties of the resulting magnet. The C content of the magnet powder can be measured by combustion in an oxygen stream-infrared absorption method.
[0056] The magnetic powder according to this embodiment may be produced by the method for producing the R-T-B magnetic powder according to the above embodiment.
[0057] The applications of the magnet powder according to this embodiment are not particularly limited, but it can be suitably used, for example, in the production of sintered magnets and bonded magnets. EXAMPLES
[0058] The present disclosure will be specifically described below based on examples, but the present disclosure is not limited to these.
[0059] <Example 1> [Preparation of iron powder] 101.8g of iron nitrate and 14.9g of calcium nitrate were dissolved in 819mL of water to obtain an aqueous solution. 441mL of 1mol potassium hydroxide aqueous solution was added dropwise to the resulting aqueous solution while stirring to obtain a suspension. The suspension was collected by filtration, washed, and then dried overnight in air at 120℃ in a hot air drying oven to produce iron oxide powder. The Fe oxide powder was reduced in a hydrogen stream at 500℃ for 6 hours to produce iron powder.
[0060] [Magnetic powder production] (Heat treatment process) 0.48 g of iron powder, 0.60 g of neodymium powder, 2.07 g of lithium chloride powder, and 0.10 g of boron powder were placed in an iron crucible and heat-treated in an Ar atmosphere at 800° C. for 3 hours to obtain an Nd—Fe—B alloy powder.
[0061] (Cleaning process) The obtained Nd-Fe-B alloy powder was washed with water as a washing liquid to remove lithium chloride.
[0062] (Vacuum drying process) The Nd-Fe-B alloy powder from which the lithium chloride had been removed was substituted with acetone for water, and then vacuum-dried at room temperature (20°C) to obtain magnet powder.
[0063] [Measurement of average particle size, particle size distribution range and circularity of magnet powder] The obtained Nd-Fe-B magnet powder and a thermosetting resin (epoxy resin) were mixed in approximately equal amounts by volume and thoroughly mixed to obtain a mixture. The obtained mixture was applied onto a sample stage (pin stub) for FIB (Focused Ion Beam) and vacuum degassed. The mixture was then heated at 120°C for 1 hour using a hot plate to harden the mixture and obtain a hardened product. The surface of the hardened product was then dry-polished with abrasive paper. The hardened product was first roughly polished with coarse abrasive paper (#600), then further polished with medium-roughness abrasive paper (#1200), and finally polished with fine abrasive paper (#3000), to obtain a measurement sample with a mirror-finished polished surface. The obtained measurement sample was observed with a SEM (Scanning Electron Microscope) to obtain an SEM image. The observation magnification was 10,000 times.
[0064] Next, 300 particles were randomly selected from the magnetic powder particles that could be confirmed in the SEM image. The area S and perimeter L of the magnetic powder particles selected were measured using image analysis and image measurement software. Then, the particle diameter D, particle size distribution width, and circularity coefficient, which are respectively defined by the following formulas (1) to (3), were calculated.
[0065]
number
[0066] D 10 , D 50 and D. 90 are the particle diameters at which the cumulative frequency is 10%, 50%, and 90%, respectively, in the area-based cumulative particle diameter distribution curve of 300 magnet powder particles. The area-based average value of the particle diameters D of the 300 magnet powder particles was taken as the average particle diameter of the magnet powder, and the number-based average value of the circularity coefficients of the 300 magnet powder particles was taken as the circularity of the magnet powder. The results are shown in Table 1.
[0067] [NdFe 14 Check for the presence of single crystal particles of B] A measurement sample with a mirror-finished polished surface was obtained in the same manner as in the measurement of the average particle size, particle size distribution width, and circularity of the magnet powder. The measurement sample was sliced by focused ion beam processing. The obtained slice was observed under a TEM (Transmission Electron Microscope). The observation magnification was 50,000 times. The selected area diffraction image of the TEM observation was spot-shaped, and Nd2Fe 14 If the crystal structure of B matches the P42 / mmm characteristic, the magnet powder is Nd2Fe 14 It was determined that the powder had single crystal particles of B. The results are shown in Table 1.
[0068] [Measurement of Ca content] The Ca content in the obtained magnet powder was measured using ICP-AES (Inductively Coupled Plasma Atomic Emission Spectroscopy), and the results are shown in Table 1.
[0069] <Examples 2 to 4, 6> Magnet powder was obtained in the same manner as in Example 1, except that the cleaning solution shown in Table 1 was used instead of water. The average particle size, particle size distribution width, and circularity of the magnet powder were measured in the same manner as in Example 1, and the NdFe14 The presence or absence of single crystal particles of B was confirmed, and the Ca content was measured. The results are shown in Table 1.
[0070] In Table 1, EG stands for ethylene glycol, FA stands for formamide, and DMF stands for dimethylformamide.
[0071] <Example 5> Magnet powder was obtained in the same manner as in Example 1, except that the cleaning solution shown in Table 1 was used instead of water. The average particle size, particle size distribution width, and circularity of the magnet powder were measured in the same manner as in Example 1, and the NdFe 14 The presence or absence of single crystal particles of B was confirmed, and the Ca content was measured. The results are shown in Table 1.
[0072] [Measurement of Cl content] The Cl content in the obtained magnet powder was measured using ICP-AES (Inductively Coupled Plasma Atomic Emission Spectroscopy), and was found to be 12,900 ppm by mass.
[0073] [Evaluation of magnetic properties] The mass magnetization and coercivity of the obtained magnet powder were evaluated using a VSM (Vibrating Sample Magnetometer) as follows. That is, the magnetization of the magnet powder was measured by applying an external magnetic field of 1592 kA / m (20 kOe) to -1592 kA / m (-20 kOe), and each value was obtained from the obtained demagnetization curve. The mass magnetization (σ 20kOe The magnetic field strength was 102 emu / g. The coercive force was 1.1 kOe.
[0074] [Table 1] [Industrial Applicability]
[0075] According to a method for producing an RTB based magnet powder according to one aspect of the present invention, it is possible to produce magnet powder having a small average particle size and a narrow particle size distribution.
Claims
1. A heat treatment step is provided for obtaining an R-T-B type alloy powder by heating a composition containing a rare earth metal element R, a transition metal element T, boron B, and lithium chloride at a temperature equal to or higher than the melting point of the lithium chloride, The rare earth metal element R is at least one selected from the group consisting of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu; A method for producing an R-T-B system magnet powder, wherein the transition metal element T is at least one selected from the group consisting of Fe, Ni, Co, Cr and Mn.
2. The method for producing R-T-B system magnet powder according to claim 1 , further comprising a washing step of washing the R-T-B system alloy powder with a washing liquid in which the lithium chloride is dissolved.
3. The method for producing R-T-B system magnet powder according to claim 2 , wherein the cleaning liquid contains a solvent that does not have a hydroxy group.
4. 3. The method for producing R-T-B system magnet powder according to claim 2, wherein the cleaning liquid contains at least one selected from the group consisting of formamide and dimethylformamide.
Citation Information
Patent Citations
Production of alloy powder for magnet
JP1998280002A
Manufacture of alloy powder
JP1999189811A
R-t-b based permanent magnet
JP2017157832A
Polycrystal rare earth transition metal alloy powder and method for producing the same
JP2020045544A
METHOD FOR PRODUCING RFeB SINTERED MAGNET AND RFeB SINTERED MAGNET PRODUCED THEREBY
WO2014142137A1